Changes in smoker characteristics in England between 2008 and 2017 - Garnett, Claire (Addiction, 2020)
AIMS: At a time of declining smoking prevalence in England, it is useful to document any changes in the characteristics of smokers. This has implications for targeting tobacco control policies and interventions. This study compared the characteristics of smokers from 2008 to 2017 to assess changes in smoking and quitting patterns and socio‐demographic profile. DESIGN AND SETTING: Analysis of annual trends in results from repeated cross‐sectional surveys of representative samples of the population in England from 2008 to 2017. PARTICIPANTS: The study included 208 813 adults aged 16+. MEASUREMENTS: Information was gathered on age, sex, social grade and region, cigarette consumption, cigarette dependence as measured by time to first cigarette of the day, daily smoking, smoking roll‐your‐own cigarettes, attempts to cut down, use of an e‐cigarette or nicotine replacement therapy, attempts to cut down or quit, use of support in quit attempts and whether the quit attempt was abrupt. FINDINGS: During the period, mean daily cigarette consumption [B = –0.30, 95% confidence interval (CI) = –0.33 to −0.27] and the time to first cigarette score decreased (B = –0.03, 95% CI = –0.03 to −0.02). The proportion of smokers attempting to cut down or quit decreased (odds ratio (OR) range = 0.96–0.97, 95% CI range = 0.95–0.97). Use of behavioural support [odds ratio (OR) = 0.89, 95% CI = 0.86–0.92] or no support decreased (OR = 0.98, 95% CI = 0.96–0.99), while use of pharmacological support, including e‐cigarettes, increased (OR = 1.04, 95% CI = 1.02–1.05). There was no significant change in the difference in social grade between smokers and non‐smokers comparing 2008 with 2017. Changes in smoking and quitting behaviour were independent of changes in socio‐demographic characteristics. CONCLUSIONS: Between 2008 and 2017 in England, smokers appear to have become less dependent on cigarettes but less likely to try to quit or cut down. Of those who tried to quit, fewer used behavioural support and more used pharmacological support. The proportion from more disadvantaged backgrounds did not change significantly.